Institutional Process in the Implementation of Special Autonomy: A Historical Institutionalism Analysis of Papua Barat Daya Province, Indonesia - Yakob Kareh; Sukri Sukri; Muh. Akmal Ibrahim (Journal Social Civilecial, 2025)
This study examines how institutional processes in Papua’s Special Autonomy (Otsus) have formed, evolved, and reproduced over more than two decades under Law No. 21/2001 and its 2021 revision. Persistent weakening of MRP representational functions, vertical-horizontal fragmentation, and stagnation in Indigenous Papuan empowerment indicate that Otsus implementation cannot be explained solely through formal institutional design. Drawing on Historical Institutionalism, this study analyses three dimensions of institutional effectiveness: regulatory and procedural clarity, consistency of fund-implementation flows, and effectiveness of coordination and evaluation forums. A qualitative historical-institutional case-study design was applied using process tracing and within-case analysis. Data were collected through in-depth interviews with provincial officials, former Otsus drafters, customary leaders, MRP representatives, NGO actors, academics, and Indigenous Papuan community representatives, supported by document analysis of Otsus laws, implementing regulations, presidential regulations, provincial budget documents, audit reports, and media archives. Coding was conducted using NVivo and validated through triangulation and member checking. The findings show strong normative-administrative clarity, with regulatory foundations scoring 9/10, but weak operational-sequential clarity, with planning sequence, budget flow, and evaluation scoring 4, 3, and 3. Implementation consistency is reproductive rather than transformative: regulations, work units, master plans, and budgets are reproduced, while substantive empowerment remains limited. Layering dominates institutional change, producing old-pattern persistence in MRP functions and budget-authority structures. Coordination forums operate as adaptation channels but fail as policy-feedback mechanisms. The study contributes the concepts of reproductive continuity and transformative continuity to explain why formal stability has not produced substantive institutional transformation in a newly established peripheral province.